The other family : a novel - Staub, Wendy Corsi (William Morrow, an imprint of HarperCollins Publishers, 2022)
It's the perfect home for the perfect family: pretty Nora Howell, her handsome husband, their two teenage daughters, and lovable dog. As California transplants making a fresh start in Brooklyn, they expected to live in a shoebox, but the brownstone has a huge kitchen, lots of light, and a backyard. The catch: its previous residents were victims of a grisly triple homicide that remains unsolved. Soon, peculiar things begin happening. The pug is nosing around like a bloodhound. Nora unearths a long-hidden rusty box in the flowerbed. Oldest daughter Stacey, obsessed with the family murdered in their house, pokes into the bloody past and becomes convinced that a stranger is watching the house. Watching them. She's right. But one of the Howells will recognize his face. Because one of them has a secret that will blindside the others with a truth that lies shockingly close to home, and to this one's terrifying history.